Regulatory choices in global financial markets: restoring the role of aggregate utility in the shaping of market supervision - Peik Granlund (Bank of Finland, 2008)
In financial market studies, public supervision has rarely been found to have any effects on financial market development. This is true, even though the primary objective of supervisory legislation is the limitation of market failures and externalities. Studies conducted by eg the World Bank and La Porta & al imply that whereas private enforcement contributes to financial market development, there is limited evidence that public supervision does the same. The objective of the paper is to empirically investigate the relation between public supervision and financial market development. This is done by focusing on major legislative features directing the supervisor and hence affecting market participant activities. The markets investigated comprise banks, investment firms, investment fund companies and listed companies in the United States, United Kingdom, Sweden, Finland, Poland and Estonia for the years 1996 to 2005. The results suggest that certain features of public supervision correlate with financial market development. Strong legal obligations for the supervisor to develop legislation correlate significantly with higher company market values. Emphasizing economic aspects in the formulation of supervisory objectives corresponds with higher market profitability. Furthermore, severe monetary sanctions applicable to company directors correlate negatively with market growth. Unexpectedly, the same is true for a high degree of supervisory independence. The results imply links between public supervision and financial market development in a manner not always in line with previous research. Why this is the case, requires further investigation. One possible explanation may be methodological, based on the fact that in the present study legislative features are perceived in a conceptual rather than a technical manner.
URN:NBN:fi:bof-20140807561
Keywords: G28; K23; O16; 330; financial institution; regulation; supervision; utility